2020
DOI: 10.3389/fpsyg.2020.571852
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Modal Correspondences Between Temperature and Taste Attributes

Abstract: Temperature is an important characteristic of food and drink. In addition to foodintrinsic temperature (i.e., serving temperature), consumers often experience foodextrinsic temperature (e.g., physical warmth). Emerging research on cross-modal correspondence has revealed that people reliably associate temperature with other sensory features. Building on the literature on cross-modal correspondence and sensation transference theory, the present study aimed to reveal mental representations of temperature-taste co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 65 publications
(128 reference statements)
0
22
0
Order By: Relevance
“…First, the temperature in the current research was generally in the comfortable range; however, research showed that thermal comfort (comfortable vs. uncomfortable) would interact with ambient temperature in influencing people's behaviors (Motoki, Saito, Nouchi, Kawashima, & Sugiura, 2019; Motoki, Saito, Nouchi, & Sugiura, 2020). Future research could investigate temperature across a wider spectrum (i.e., both comfortable and uncomfortable temperature range) to detect whether the effect will change when the temperature is uncomfortable.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…First, the temperature in the current research was generally in the comfortable range; however, research showed that thermal comfort (comfortable vs. uncomfortable) would interact with ambient temperature in influencing people's behaviors (Motoki, Saito, Nouchi, Kawashima, & Sugiura, 2019; Motoki, Saito, Nouchi, & Sugiura, 2020). Future research could investigate temperature across a wider spectrum (i.e., both comfortable and uncomfortable temperature range) to detect whether the effect will change when the temperature is uncomfortable.…”
Section: Discussionmentioning
confidence: 82%
“…First, the temperature in the current research was generally in the comfortable range; however, research showed that thermal comfort (comfortable vs. uncomfortable) would interact with ambient temperature in influencing people's behaviors (Motoki, Saito, Nouchi, Kawashima, & Sugiura, 2019;Motoki, Saito, Nouchi, & Sugiura, 2020).…”
Section: Future Research Directionmentioning
confidence: 82%
“…Energy intake was measured by the same gold-standard procedure (weighing of the consumed foods) in all the included studies, but the food selected and the timing, number, and nature of the meals (buffet or meals with less than three items) varied considerably between the studies included. Moreover, temperature of the items served may jeopardize the relationships between palatability, thermal comfort, and body temperature potentially affecting intake [40][41][42][43]. However, the range of temperatures was large (cold, warm, and/or room temperature) and often weakly reported.…”
Section: Discussionmentioning
confidence: 99%
“…offered as one of the explanatory mechanisms behind the phenomenon (Kantono et al, 2016;Motoki et al, 2020b;Motoki, Saito, Nouchi, & Sugiura, 2020a;Motoki & Velasco, 2021;Reinoso-Carvalho, Dakduk, Wagemans, & Spence, 2019;Spence, 2020aSpence, , 2020bVelasco, Woods, Deroy, & Spence, 2015;Wang & Spence, 2017;Wang, Wang, & Spence, 2016). People tend to associate round shapes with sweetness and pleasant or calming feelings (or meanings) (Motoki & Velasco, 2021).…”
Section: Discussionmentioning
confidence: 99%